Operating Subsidies and the Economic Situation of Agricultural Farms in Poland in 2014-2019 - Janek, Sebastian; Czyż , Joanna; Witkowska-Dąbrowska, Mirosława (Olsztyn Economic Journal, 2021)
The purpose of this study has been to determine the role of operating subsidies in shaping the economic situation of agricultural farms in the years 2014-2019. Secondary data originating from the database of accounting books of farms aggregated by the Polish FADN were taken for our analysis. The data were processed through an analysis of the dynamics of changes in 2014-2019. The results showed that operating subsidies reached an average of between 41% and 282% of the value of income earned by family-owned farms. It was found that whether or not farms were able to earn a financial surplus without resorting to subsidies depended on the economic size of a farm. The smallest and the largest farms were unable to cover their costs and earn a profit without having access to additional sources of funds.